Use of Social Media as an Online Learning Media - Regina; Sudarsono; Clarry Sada; Y Gatot Sutapa Yuliana; Ikhsanudin; Dwi Riyanti; Y. Touvan Juni Samodra (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2023)
Since early March 2020, the Coronavirus outbreak has begun to spread in several regions of Indonesia. The government is starting to be aware of the spread of the virus by tightening supervision of the movement of people from one place to another within local, national, and international areas to avoid transmission. The government also issued policies to maintain distance, wear masks, and wash hands to stop the spread. Many office tasks and teaching and learning processes are carried out from home. This requires teachers to be able to utilize internet-based media for their teaching, such as social media, which is popular in the community. Therefore, in this PKM, we provide additional benefits from social media to teachers at SMP Negeri 1 Sungai Ambawang who teach their students from home. PKM was held offline on Saturday, October 10, 2020, and was attended by 28 participants. This activity has provided enlightenment and alternatives for teachers in teaching